2015
DOI: 10.1007/s10347-015-0427-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis makes the impossible come true: intersecting beds in calcareous turbidites

Abstract: produce rhythmic bedding lacking any relation to primary sedimentary signals is demonstrated. The Miocene succession discussed here shows two cemented sets of beds with different inclinations, one parallel to the sedimentary layering, the other, coeval, but in an oblique direction. These two sets merge and do not show distinct boundaries, thus indicating synchronous cementation. It is interpreted that minor early synsedimentary tectonic stress introduced an oblique anisotropy. During early differential diagene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The importance of shallow diagenetic CaCO 3 redistribution (differential diagenesis) in the formation of LMA has been shown for various depositional environments and geological periods (e.g. Westphal et al ., 2015; Nohl & Munnecke, 2019; Nohl et al ., 2019; Su et al ., 2020). In the absence of variations in the composition of terrigenous material, variations in calcite and aragonite input are still possible but will not be detectable in the ratio of diagenetically inert elements such as Ti and Al (Westphal et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of shallow diagenetic CaCO 3 redistribution (differential diagenesis) in the formation of LMA has been shown for various depositional environments and geological periods (e.g. Westphal et al ., 2015; Nohl & Munnecke, 2019; Nohl et al ., 2019; Su et al ., 2020). In the absence of variations in the composition of terrigenous material, variations in calcite and aragonite input are still possible but will not be detectable in the ratio of diagenetically inert elements such as Ti and Al (Westphal et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It involves an intense mass exchange with at least a major CaCO 3 import at one site, as well as a major CaCO 3 export from close proximity. It may lead to the differentiation into two lithologies which often do not follow original sedimentary structures and sometimes even cross‐cut them (Bathurst, 1971; Munnecke & Samtleben, 1996; Westphal et al ., 2015; Nohl & Munnecke, 2019). The possibility of diagenetic differentiation into two lithologies entirely through a diagenetic pathway therefore puts in question the reliability: (i) of the lithological rhythmicity (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical spatial heterogeneity, especially, can originate from the combined effects of small depositional changes and pressure-related processes, which can lead to stratified lithological alternations. It has been shown that post-depositional heterogeneities, induced from a sediment that was virtually homogeneous to begin with, can create strictly diagenetic lithological alternations (see Westphal et al, 2015, especially their Fig. 2 for a visual demonstration in calcareous sediments).…”
Section: Introductionmentioning
confidence: 99%